Kontribusi Honorifik Bahasa Madura terhadap Pengayaan Sapaan Santun Berbahasa Mahasiswa STKIP PGRI Sumenep - Suhartatik, Suhartatik; Hodairiyah, Hodairiyah; Arifah, Siti (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This study discussed about the use of the Madurese speech level used by students of STKIP PGRI Sumenep in communicating at campus. The purpose of this study was to describe the use of levels of the Madurese language (ondhâgghâ bhâsa) as a form of language politeness (honorific) which was very important in speaking manners. The method was qualitative descriptive method with data collection techniques using the listening proficient technique. The results of this study found several personal name greeting words, personal pronoun greeting words, academic title greetings, and job titles and ranks used by students according to the level of the Madurese language, namely, according to the kinds there are three (3); bhâsa enjâ 'iyâ, bhâsa engghi enten, and bhâsa èngghi bhunten and according to the ups and downs / sorot sandherrâ language is divided into three (3) parts, namely; bhâsa andhâp / low language, bhâsa tèngnga'an / middle language, and bhâsa tèngghi / high language. This research is hoped that students will be able to know the greeting words according to the level of the Madurese language correctly so that later they can communicate well and politely when dealing with lecturers or leaders on campus, especially at STKIP PGRI Sumenep Madura.